Reconstructing a Submerged Villa Maritima: The Case of the Villa dei Pisoni in Baiae - Barbara Davidde Petriaggi; Michele Stefanile; Roberto Petriaggi; Antonio Lagudi; Raffaele Peluso; Paola Di Cuia (Heritage, 2020)
Among the activities planned for the MUSAS Project, the digital reconstruction of the underwater sites constitutes a particular challenge, requiring strong cooperation between archaeologists and technicians. The case of the Villa dei Pisoni in Baiae, one of the richest in the Phlaegrean territory, is particularly interesting: the architectural remains, already documented in the 1980s and now inserted in one of the diving spots of the Underwater Park of Baiae, are disseminated on a huge surface, including quays, thermal complexes, a fishpond, and a large, luxurious viridarium. The effort required for the digital reconstruction of the ancient villa improved the previous knowledge and the lack of documentation even in a well-known site. In this paper, we will retrace the long path from the 3D reconstruction of the archaeological remains to the virtual architectural model of the villa, the numerous challenges, doubts, and uncertainties in the creation of the original spaces, and the support offered by the ancient sources, both literary and iconographic, in solving archaeological problems.